A unified perspective on the adoption of online teaching in higher education during the COVID-19 pandemic. Issue 2 (6th January 2021) - Mittal, Amit; Mantri, Archana; Tandon, Urvashi; Dwivedi, Yogesh K.
Abstract : Purpose: The study aims to develop a theoretical model that highlights the determinants of the adoption of online teaching at the time of the outbreak of COVID-19. This study adopted a time-series analysis to understand the factors leading to the adoption of online teaching. Design/methodology/approach: Empirical data were gathered from 222 university faculty members by using an online survey. In the first phase, data were collected from those faculty members who had no experience of conducting online classes but were supposed to adopt online teaching as a result of the COVID-19 pandemic and subsequent lockdown. After two weeks, a slightly modified questionnaire was forwarded to the same group of faculty members, who were conducting online classes to know their perception regarding the adoption and conduct of online teaching. Findings: Both the proposed conceptual frameworks were investigated empirically through confirmatory factor analysis and structural equation modeling. Significant differences were found in the perceptions of faculty members regarding before and after conducting classes through online teaching. Originality/value: This study contributes to the literature by presenting and validating a theory-driven framework that accentuates the factors influencing online teaching during the outbreak of a pandemic. This research further extends the unified theory of acceptance and use of technology by introducing and validating three new constructs, namely: facilitative leadership, regulatory support and project team capability. Based on the findings, practical insights are provided to universities to facilitate adoption, acceptance and use of online teaching during a health-care emergency leading to campus lockdowns or the imposition of restrictions on the physical movement of people.